1995
DOI: 10.1002/bdd.2510160705
|View full text |Cite
|
Sign up to set email alerts
|

Influence of leucine on intestinal baclofen absorption as a model compound of neutral α‐aminoacids

Abstract: The inhibitory effect of the essential alpha-aminoacid L-leucine on the intestinal absorption of the antispastic drug baclofen was examined by means of an in situ rat gut perfusion technique. When 0.5 mM baclofen solutions were perfused in the presence of increasing concentrations of the aminoacid (5-100 mM), the apparent absorption rate constant of the drug decreased as the initial leucine concentration increased. Higher leucine concentrations however did not completely abolish the absorption of the drug (at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The absorption rate pseudoconstants, k ap , calculated according to eq 1 are also given. According to these results, the baclofen absorption rate pseudoconstant was significantly reduced relative to that found in the presence of 100 mM leucine (k ap ) 0.220 ( 0.050 h -1 ), 7 in the presence of 100 mM taurine (k ap ) 0.561 ( 0.063 h -1 ) and in the presence of 100 mM GABA (k ap ) 0.650 ( 0.010 h -1 ), 31 respectively. This result confirms that more than one carrier system is involved in baclofen absorption.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The absorption rate pseudoconstants, k ap , calculated according to eq 1 are also given. According to these results, the baclofen absorption rate pseudoconstant was significantly reduced relative to that found in the presence of 100 mM leucine (k ap ) 0.220 ( 0.050 h -1 ), 7 in the presence of 100 mM taurine (k ap ) 0.561 ( 0.063 h -1 ) and in the presence of 100 mM GABA (k ap ) 0.650 ( 0.010 h -1 ), 31 respectively. This result confirms that more than one carrier system is involved in baclofen absorption.…”
Section: Discussionmentioning
confidence: 72%
“…In our opinion, the second possibility is much more realistic, as is corroborated by the fact that baclofen absorption is better described only by the MichaelisMenten equation. Moreover, recent inhibition studies with neutral R-amino acids 7,8 demonstrated that baclofen could be transported in the rat small intestine using their carrier system, so the existence of a second carrier system not inhibited by taurine is highly probable. Another fact that corroborates the existence of two carrier systems for baclofen absorption is the different values obtained of K mi and K i for taurine (Table 5).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For instance, quantitation of amino acids in proteins and peptides provides answers as to what protein or protein fragment we have. Measurement in biological fluids of amino acids that can be used to predict the likely course of a disease and to monitor and assist in the management of this disease is a strategy commonly applied for understanding the physiological state of a tissue [1][2][3][4][5][6][7][8][9][10]. Separation of individual amino acid enantiomers is often a critical step in such diverse fields as geological dating [11][12][13][14], food chemistry [6,15], physiology [2,16], and protein/ peptide-based drug development [17].…”
Section: Introductionmentioning
confidence: 99%